2001
DOI: 10.1002/imhj.1004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychopathology and attachment in toddlers of heavy cocaine‐using mothers

Abstract: The purpose of this study is to examine the relationships among maternal psychopathology, early sensitive caregiving, and security of attachment in a sample of cocaine-using women from environments with high contextual risks that include poverty, low educational attainment, minority status, and single parenthood. Thirty-five women and their offspring participated in the study. Maternal psychopathology, including Axis I and Axis II disorders, was assessed during the prenatal period via a selfreport clinical mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
1
10

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 43 publications
2
47
1
10
Order By: Relevance
“…To date, early parenting has been studied in relation to the psychosocial characteristics of the caregiver (Crockenberg & Leerkes, 2003;Espinosa, Beckwith, Howard, Tyler, & Swanson, 2001), experiences of daily stress (Hummer & Samuels, 1988), family relationships (Cox & Paley, 2003), parenting beliefs (NICHD ECCRN, 2004), parental internal working models (Crockenberg & Leerkes, 2003), and influence of child temperament (Belsky, 1984;Leerkes & Crockenberg, 2002). By comparison, there has been limited examination of the psychophysiological correlates of sensitive and nonharsh parenting behaviors (Bardi, French, Ramirez, & Brent, 2004;Leckman & Herman, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…To date, early parenting has been studied in relation to the psychosocial characteristics of the caregiver (Crockenberg & Leerkes, 2003;Espinosa, Beckwith, Howard, Tyler, & Swanson, 2001), experiences of daily stress (Hummer & Samuels, 1988), family relationships (Cox & Paley, 2003), parenting beliefs (NICHD ECCRN, 2004), parental internal working models (Crockenberg & Leerkes, 2003), and influence of child temperament (Belsky, 1984;Leerkes & Crockenberg, 2002). By comparison, there has been limited examination of the psychophysiological correlates of sensitive and nonharsh parenting behaviors (Bardi, French, Ramirez, & Brent, 2004;Leckman & Herman, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Psychological symptoms that occur after chronic use include somatic problems (Johanson et al 1999;Watson et al 1992), eating disorders (Ross-Durow and Boyd 2000), anxiety and depression (Beckwith et al 1999;Falck et al 2002). Associations between chronic cocaine use and conditions such as obsessive-compulsive disorder (Crum and James 1993), paranoia (Espinosa et al 2001;Lejoyeux et al 2000), schizophrenia (Bowers et al 2001), and antisocial personality disorder (Falck et al 2004;Ladd and Nancy 2003) have also been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Negative effects of psychological symptoms on parenting include less sensitive maternal care giving behavior, experience of parenting stress and poor infant attachment (Eiden et al 2006;Espinosa et al 2001;Howard et al 1195;Minnes et al 2005;Sheinkopf et al 2006) and less optimal infant cognitive (Singer et al 1997) and language outcomes (Marques et al 2007). Despite the known negative effects of psychological distress on parenting among cocaine using women, very little is known about the natural history of mental health symptoms among cocaine using mothers (Jantzen et al 1998;Minnes et al 2000Minnes et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Dada que la presencia de patología dual puede llegar a ser muy elevada y que las madres afectadas de trastornos mentales en ausencia de drogodependencia pueden considerarse por sí mismas un colectivo vulnerable [98][99][100] , se trataría en estos casos de un doble hándicap para la madre y para el niño. En efecto, la presencia de alteraciones diversas en los Ejes I (por ejemplo, trastornos de corte afectivo o psicótico) y II (trastorno antisocial o límite) según DSM parece relacionarse con peores habilidades parentales y/o peor pronóstico infantil 95,101,102 .…”
Section: Factores Psicosocialesunclassified